Modeling of the deformation behavior of single crystalline Nickel-based superalloys under thermal mechanical loading. (April 2017) - Wilhelm, F.; Affeldt, E.; Fleischmann, E.; Glatzel, U.; Hammer, J.
Highlights: The threshold stress concept is suitable to describe the creep behavior of dual phase alloys. The Lagneborg-Bergmann-plot is used to assign the strength of the matrix and the γ′-phase. The deformation behavior can be modelled by Hooke's Law, Ramberg-Osgood equation and the threshold stress concept. The dwell time increases the time dependent deformation and decreases the lifetime to a large extent. Abstract: The focus of this paper is the simulation of the thermal-mechanical fatigue behavior (TMF) of two single crystalline Nickel-based superalloys in a temperature range between 400 °C and 980 °C. The newly developed rhenium-free alloy Astra-3OptW and the rhenium-free alloy CMSX-6 are analyzed concerning the basic deformation mechanisms, i.e. elasticity, time-independent and time-dependent plasticity contributing to hardening. In detail, the relevant parameters for high temperature deformation are identified from isothermal creep experiments and used in a numerical model to simulate the deformation behavior under instationary thermal and mechanical loading. Special attention is focused on the determination of the hardening by the second phase (γ′-precipitates) and their influence on time-dependent deformation and relaxation mechanisms. Therefore, the parameters describing the stress and temperature dependence of the creep rate (i.e. stress exponent n and activation energy Q) are interpreted in terms of a threshold stress taking into account the hardening contribution of the γ′-phase. Thus, only a reduced effective stress is active for plastic deformation. Particular attention is focused on the accurate determination of the threshold stress as a function of temperature and applied stress from the Langeborg-Bergmann-plot. The comparison of the simulated TMF-deformation to the experimental TMF-data clearly indicates the accuracy of the model in predicting the resulting stresses induced by instationary thermal and mechanical loading.